Eye‐Tracking Reveals Absent Repetition Learning Across the Autism Spectrum: Evidence From a Passive Viewing Task. Issue 11 (30th August 2020) - Gaigg, Sebastian B.; Krug, Marie K.; Solomon, Marjorie; Roestorf, Amanda; Derwent, Claire; Anns, Sophie; Bowler, Dermot M.; Rivera, Susan; Nordahl, Christine Wu; Jones, Emily J. H.
Abstract : In the domain of memory, autism is characterized by difficulties in explicitly remembering the specific order of stimuli, whereas implicit serial order memory appears to be preserved. This pattern is of considerable interest because serial order memory is known to play a critical role in children's language development. Currently, however, few paradigms exist that can effectively probe serial order memory across heterogeneous groups of children, including those who are minimally verbal. We present two experiments, involving 39 adults (20 ASD; 19 TD) and 130 children (86 ASD; 44 TD), that address this issue using an eye‐tracking paradigm, which simply required participants to "watch out for a bunny" that appeared in repeating sequences of screen locations. The adults in Experiment 1 all had normative IQs, whereas Experiment 2 included children with and without substantial language and intellectual difficulties. In both experiments gaze latencies and anticipatory fixations to the bunny indicated reliable repetition learning effects in the TD but not the ASD groups. Importantly, we were able to acquire reliable data from around half of the children with significant language impairments in Experiment 2, indicating that the paradigm can shed light on important learning processes in this underrepresented group. We discuss the implications of these findings for theories of memory in ASD as well as for the utility of eye‐tracking technology to probe repetition learning effects in autism. Autism Res 2020, 13 : 1929‐1946. © 2020 The Authors. Autism Research published by International Society for Autism Research and Wiley Periodicals LLC. Lay Summary: Remembering the specific order of stimuli plays an important role in language development and is thought to be a source of difficulty for autistic individuals. Research in this area, however, rarely includes autistic participants who are minimally verbal. Here we develop an eye‐tracking paradigm that demonstrates serial order learning difficulties across the autism spectrum. We discuss the implications of these findings for our understanding of the role of memory difficulties in the varied language profiles across the autism spectrum.